Artemisia smithii patches form fertile islands and lead to heterogeneity of soil bacteria and fungi within and around the patches in alpine meadows of the Qinghai-Tibetan Plateau - Yang, Hang; Yu, Xiaojun; Song, Jianchao; Wu, Jianshuang (Frontiers in Plant Science, 2024)
Herbivore-avoided plant patches are one of the initial characteristics of natural grassland degradation. These vegetation patches can intensify the spatial heterogeneity of soil nutrients within these grasslands. However, the effects of nonedible plant patch on the spatial heterogeneity of microorganisms have not been sufficiently studied in alpine meadows of the Qinghai-Tibetan Plateau, especially patches formed by herbaceous plants. To answer this question, soil nutrients, plant assembly and microbial communities were measured inside, around, and outside of Artemisia smithii patches. These were 0 m (inside the patch), 0-1 m (one meter from the edge of the patch), 1-2 m (two meters from the edge of the patch), 2-3 m (three meters from the edge of the patch), and >30 m (non-patch grassland more than 30 meters from the edge of the patch). Our results showed that A. smithii patches accumulated more aboveground biomass (AGB) within the patches (0 m), and formed fertile islands with the soil around the patches. Additionally, A. smithii patches increased soil bacterial diversity within (0 m) and around (0-1 m) the patches by primarily enriching copiotrophic bacteria (Actinobacteria), while the diversity of fungal communities increased mainly in the 0-1 m area but not within the patches.Bacterial community diversity was driven by pH, urease, nitrate nitrogen (NO3⁻-N)NO3⁻-N, and microbial biomass carbon (MBC)MBC. The contents of soil water (SWC)SWC, soil organic matter (SOM)SOM, urease, NO3⁻-N, and MBC were the main factors influencing the diversity of the fungal community. This study elucidates the vegetation, nutrients, and microbial heterogeneity and their interrelationships, which are observed in fertile islands of herbivore-avoided plant patches in alpine meadows, and provides further insights into the spatial pattern of nutrients in patchy degraded grasslands.